Introduction - narrative and aesthetic experience in ancient Greece - Grethlein, Jonas; Huitink, Luuk; Tagliabue, Aldo (Experience, narrative, and criticism in ancient Greece, 2020)
This volume aims to pursue a new approach to ancient Greek narrative beyond the taxonomies of structuralist narratologies, focusing on the phenomenal and experiential dimension of our response to narrative and triangulating ancient narrative with ancient criticism and cognitive approaches. The introductory chapter offers an overview of the theoretical frameworks in play and briefly encapsulates how each chapter seeks to contribute to a multifaceted picture of narrative and aesthetic experience. Immersion and embodiment emerge as central concepts and common threads throughout, helping to establish a more comprehensive understanding of ancient narrative and ancient reading habits, as manifested in Greek criticism and rhetorical theory, though the individual chapters tackle a wide range of narrative genres, broadly understood, from epic, historiography, and the novel to tragedy and early Christian texts, and other media, such as dance and sculpture.
Gesehen am 22.07.2020